Dendrodendritic Synapses in the Mouse Olfactory Bulb External Plexiform Layer - Bartel, Dianna L. (J Comp Neurol, 2015)
Odor information relayed by olfactory bulb projection neurons, mitral and tufted cells (M/T), is modulated by pairs of reciprocal dendrodendritic synaptic circuits in the external plexiform layer (EPL). Interneurons, which are accounted for largely by granule cells, receive depolarizing input from M/T dendrites and in turn inhibit current spread in M/T dendrites via hyperpolarizing reciprocal dendrodendritic synapses. Because the location of dendrodendritic synapses may significantly affect the cascade of odor information, we assessed synaptic properties and density within sublaminae of the EPL and along the length of M/T secondary dendrites. In electron micrographs the M/T to granule cell synapse appeared to predominate and were equivalent in both the outer and inner EPL. However, the dendrodendritic synapses from granule cell spines onto M/T dendrites, were more prevalent in the outer EPL. In contrast, individual gephyrin-IR puncta, a postsynaptic scaffolding protein at inhibitory synapses used here as a proxy for the granule to M/T dendritic synapse was equally distributed throughout the EPL. Of significance to the organization of intrabulbar circuits, gephyrin-IR synapses are not uniformly distributed along M/T secondary dendrites. Synaptic density, expressed as a function of surface area, increases distal to the cell body. Furthermore, the distributions of gephyrin-IR puncta are heterogeneous and appear as clusters along the length of the M/T dendrites. Consistent with computational models, our data suggest that temporal coding in M/T cells is achieved by precisely located inhibitory input and that distance from the soma is compensated with an increase in synaptic density.